Hubungan antara Kekuatan Maksimal terhadap Tinggi Lompatan dan Kelincahan Atlet Bulutangkis - Fauzi, Muhammad Jausyaq; Imanudin, Iman; Ugelta, Surdiniaty (Universitas Nusantara PGRI Kediri, 2025)
This study aims to determine the relationship between maximum strength and jump height and agility of badminton athletes. This study uses a quantitative descriptive approach method with a correlational type. The sample in this study was the UPI Badminton UKM consisting of 12 athletes. The instruments used in this study were (1) Maximum strength test (maximum repetition), (2) Jump height test (Vertical jump), (3) Agility test (Shuttle run). Based on the Pearson correlation analysis, the results showed that maximum repetition had a significant positive relationship with vertical jump with a value of (r = 0.584, p = 0.065). Likewise, maximum repetition had a significant positive relationship with agility with a value of (p = -0.216, P = 0.501). However, the results of the regression analysis showed that these variables did not have a significant relationship with jump height and agility of badminton athletes. From the results of the study, it can be concluded that maximum strength training can help increase the jump height of badminton athletes. However, to improve agility, a more specific training strategy is needed that focuses on aspects other than maximal strength.